A Searching and Automatic Video Tagging Tool for Events of Interest During Volleyball Training Sessions - Salim, Fahim A.; Postma, Dees B. W.; van Delden, Robby; Reidsma, Dennis; van Beijnum, Bert-Jan; Haider, Fasih; Cengiz, Kubra (Assoc Computing Machinery, 2019)
Quick and easy access to performance data during matches and training sessions is important for both players and coaches. While there are many video tagging systems available, these systems require manual effort. This paper proposes a system architecture that automatically supplements video recording by detecting events of interests in volleyball matches and training sessions to provide tailored and interactive multi modal feedback.
Haider, Fasih/0000-0002-5150-3359; Postma, Dees/0000-0002-1108-7549; Reidsma, Dennis/0000-0002-7503-573X; Van Delden, Robby/0000-0002-6592-1199
Keywords: Human-Media Interaction; Multimodal Feedback; Gestures Analysis